2007
DOI: 10.1513/pats.200702-035aw
|View full text |Cite
|
Sign up to set email alerts
|

CD14, Endotoxin, and Asthma Risk: Actions and Interactions

Abstract: A functional single nucleotide polymorphism in the 5 genomic region of CD14 (CD14/Ϫ159) is one of the most widely tested genetic variations in relation to asthma and associated traits. The results of these studies have shown a remarkable, statistically significant heterogeneity, with some studies indicating the T-allele as a risk factor, others the C-allele, and others finding no association. Recent studies in which exposure to house-dust endotoxin or to domestic sources of microbial exposure were assessed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
5

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 35 publications
4
94
1
5
Order By: Relevance
“…26 However, the present study is the first to our knowledge that investigates possible association between CD14 and T1D. Although we cannot exclude a small effect of the tested polymorphisms in these two genes on development of T1D or allergic asthma, they do not seem to play any major role in the pathogenesis of these phenotypes in our populations.…”
Section: Tlr4 and Cd14mentioning
confidence: 54%
“…26 However, the present study is the first to our knowledge that investigates possible association between CD14 and T1D. Although we cannot exclude a small effect of the tested polymorphisms in these two genes on development of T1D or allergic asthma, they do not seem to play any major role in the pathogenesis of these phenotypes in our populations.…”
Section: Tlr4 and Cd14mentioning
confidence: 54%
“…A SNP in the 5Ј genomic region of CD14 at position Ϫ159 (Martinez, 2007) is associated with infectious diseases, asthma, and allergy (Wiertsema et al, 2006). A number of other diseases have also been linked to this polymorphism, from cardiovascular disease to autoimmunity and from infections to malignancies (Martinez, 2007).…”
Section: Cluster Of Differentiation 14 and Diseasementioning
confidence: 99%
“…In farmers' children, a bimodal effect of CD14/-260 on atopy was shown, with the direction of the effect being dependent on the type and level of environmental exposures (i.e., pets, livestock and endotoxin) [64]. Indeed, it has been suggested that either genotype has the capacity to be beneficial or detrimental in terms of atopy risk, depending upon the nature of the exposure [67]. Another polymorphism in the NOD1/CARD4 gene, which encodes an alternative intracellular receptor involved in the innate recognition of microbial components, shows a similar protective effect against allergy for T homozygosity [68].…”
Section: Immunological Mechanismsmentioning
confidence: 99%